Global Art Market in the Aftermath of COVID-19 - Elena Sidorova (Arts, 2022)
Although the global art market has often been resilient to international economic and political events, it has faced some of its biggest challenges under the influence of COVID-19. Among others, the pandemic and the accompanying restrictive administrative measures taken by world governments have significantly influenced such key economic indicators as gallery employment, art sales, and the organization of international art fairs. This Special Issue studies various economic, social, and political impacts of the COVID-19 pandemic on the global art market’s current state and future evolution.